Political Communication Experiences of Sundanese Muslim Women Politicians - Evie Ariadne Shinta Dewi; Alina Shalisa (Politik Indonesia: Indonesian Political Science Review)
This research aimed to understand the political communication of Sundanese Muslim Women Politicians in West Java in interacting with their partners in political parties and their constituents. By using a qualitative research method with a case study approach involving five informants who were selected purposively based on predetermined characteristics, the data collection technique used literature review, in-depth interviews, and non-participant observation. The results showed that: a) education from parents; b) the role of religious groups; c) the desire to overcome the problems that exist in society are the reasons for Sundanese Muslim Women Politicians to join political parties. In addition, their aim to become politicians is to become a mediator of communication between the community and the legislature and furthermore to be able to play an active role in making pro-women policies. The novelty of this research is that Sundanese Muslim women position themselves as subordinate, not to be ordinate. Another result of the research showed the motives. There are two motives of Sundanese Muslim women politicians involved in politics, namely the “because of” motive and the “In order to” motive. The political communication of Sundanese Muslim Women Politicians in West Java, especially when interacting with political party colleagues is interpreted as a process of building interpersonal relations. While political communication when interacting with constituents is interpreted as communication to build sympathy and support.